Update of the “Beijing Protocol” haplo-identical hematopoietic stem cell transplantation - Lv, Meng; Chang, Ying-jun; Huang, Xiao-jun (Bone marrow transplantation (Basingstoke), 2019)
As one of the three successful approaches for haplo-identical stem cell transplantation (haplo-SCT) in recent decades, “Beijing protocol” was based on immune tolerance induced by granulocyte colony-stimulating factor plus anti-thymocyte globulin, which included individualized conditioning regimens, novel donor selection algorithm, and risk-directed strategies for GvHD and relapse, etc. Haplo-HSCT following “Beijing protocol” demonstrated similar efficacy to HLA-matched SCT, which has become the predominant strategy for allogeneic SCT in China as well as inspiration for refinement of global practice. This review will focus on recent progressions and prospective of this approach in (1) the indications from hematological malignancies to non-malignant diseases; (2) microenvironment for hematopoietic recovery; and (3) improving T cells function.